Characteristic of Tourim Solid Waste of Harau Valley, West Sumatra. Issue 1 (November 2020) - Aziz, R; Mahmuda,; Ruslinda, Y; Dewilda, Y
Abstract: Harau Valley Tourism Region is one of the three leading tourist attractions in Lima Puluh Kota Regency. The number of visitors to the Harau Valley Tourism Area has increased every year which will also have an impact on the increase in the amount of waste generated in this region. The Harau Valley tourist area does not yet have solid waste data. Basic data is needed to plan a waste management system in an area. Based on this, research is needed regarding the generation, composition and potential of waste recycling in the Harau Valley Tourism Area. The research method used is direct measurement in the field with reference to SNI 19-3964-1994. Based on the research that has been done, the generation unit is 0.158 kg/cap./day in weight units and 3.053 Lit/cap./day in volume units. The waste composition consisted of food waste (34.29%), paper (8.39%), plastic (16.43%), textiles (1.12%), rubber (0.07%), yard waste (17, 05%), wood (12.74%), glass (3.08%), non-ferrous metals (0.92%) and others (5.91%). Recyclingpotentialforfood and yardwetwaste (77.26%), plastic (70.23%), paper (56.21%), and glass (95.69%) It is recommended to apply composting method for compostable waste, while for other recyclable waste can apply collection, separation, clensing, and packing before selling into near by shanties.